Synthesis, Characterization and Catalytic Application of Cerium(IV) Tungstosilcate - Geetha, V.; Janardanan, C. (Asian Journal of Chemistry, 2010)
Different samples of Cerium(IV) tungstosilcate has been synthesized by mixing solutions of Cerium(IV) ammonium nitrate, sodium tungstate and sodium silicate. The exchanger was characterized by capacity determination, effect of temperature and ionic radius on ion exchange capacity, pH titration curves, IR, TGA, DTA and XRD studies. Distribution behaviour towards 12 metal ions in different media and concentration has also been studied. On the basis of the distribution studies, some important binary separations were carried out using exchanger column. The H+ ions contained in the structural hydroxyl groups of the exchanger are labile and hence the material can be used as a solid acid catalyst. Esterification reaction has been chosen as a model reaction wherein ethyl benzoate has been prepared.